Who are the chronic poor? Evidence on the extent and the composition of chronic poverty in Germany - Martin Biewen (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
Based on a multiple spells approach, this paper studies the extent and the composition of chronic poverty in Germany. The results indicate that about one third of cross-sectional poverty in a given year is chronic. The characteristics that are most closely associated with long-term poverty are economic inactivity and pensioner status, while the number of children and the gender of the household head do not seem to have a systematic effect. This is in contrast to cross-sectional results where the biggest poverty risk is usually unemployment and a large number of children, while pensioners do not face particularly high poverty risks. Estimates from a multiple spells hazard model further suggest that 6% of the population have unobserved characteristics that lead to low poverty exit and high re-entry rates, making these individuals likely candidates for chronic poverty. A comparison with results for Great Britain and the United States suggests that poverty is less persistent in Germany.
Keywords: D31; C23; I32; 330; chronic poverty; poverty persistence; multiple spells; unobserved heterogeneity; Armut; Hysteresis; Mikroökonometrie; Schätzung; Deutschland